The Protective Effects of Bevacizumab in Bleomycin-Induced Experimental Scleroderma - Koca, Suleyman S.; Ozgen, Metin; Dagli, Adile F.; Gozel, Nevzat; Ozercan, Ibrahim H.; Isik, Ahmet (Wroclaw Medical Univ, 2016)
Background. The capillary networks are less dense and have irregular structures in scleroderma. These abnormalities result in lower capillary blood flow causing severe tissue hypoxia, which is a major stimulus for angiogenesis. However, current knowledge about compensatory angiogenesis is ambiguous in scleroderma. Bevacizumab is an inhibitor of vascular endothelial growth factor (VEGF). Objectives. The aim of the present study is to evaluate the protective effects of bevacizumab in bleomycin (BLM)- induced dermal fibrosis. Material and Methods. This study involved 4 groups of Balb/c mice (n = 10 per group). Mice in the control group received 100 mu L/day of phosphate-buffered saline (PBS) subcutaneously, while the other 3 groups were given 100 mu g/day of BLM (dissolved in 100 mu L PBS) subcutaneously, for 4 weeks. Mice in BLM-treated 3rd and 4th groups also received bevacizumab (1 or 5 mg/kg twice a week, intraperitoneally). At the end of the fourth week, all mice were sacrificed and blood and tissue samples were obtained. Results. The BLM applications increased the dermal thicknesses, tissue hydroxyproline contents, and alpha-smooth muscle actin-positive (alpha-SMA+) cell counts, and led to histopathologically prominent dermal fibrosis. The bevacizumab treatments decreased the tissue hydroxyproline contents and dermal thicknesses, and these improvements were more prominent at doses by which alpha-SMA+ cell counts were markedly decreased, in the BLM-injected mice. Conclusions. In our study, inhibition of VEGF with bevacizumab treatments prevented the BLM-induced dermal fibrosis suggesting that VEGF expression contributes to the pathogenesis of scleroderma.
Keywords: bevacizumab; scleroderma; dermal fibrosis; VEGF